ABOUT SCOLIOSIS – ANOTHER APPROACH (1) Physiological and physiopathological basis of scoliosis therapy - Nowotny, Janusz; Nowotny-Czupryna, Olga; Czupryna, Krzysztof; Rottermund, Jerzy (European Journal of Clinical and Experimental Medicine, 2012)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The approach to the problem of scoliosis is very different and depends primarily on the interests of authors dealing with the issue. In the literature, scoliosis is treated mostly as a static and local problem with the spine and widely seen postural effects are usually considered marginal, or even ignored. The papers describing a neuropathological aspects about disorders of spatial regulation of the body in the developing scoliosis are very rare too. Such a perception of scoliosis causes that conservative treatment of even low degree scoliosis usually is doomed to fail. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The aim of this study was to present physiological and pathophysiological basis of scoliosis therapy in terms different from most commonly presented in the literature. In this part of paper posture steering (control) system and developmental aspects of the problem in terms of physiological and pathological was first presented. Then the postural effects of growing and already developed scoliosis was presented. Attention is paid to effects of spontaneous compensation and forming the habit of improper posture. “Reprogramming” the system of postural control, making active attempts of correction ineffective and the need for early intervention leading to, among others, not to preserve the habit of improper posture was discussed as well. In the last section of this paper, attention was drawn to the fact that creating and developing scoliosis usually do not bring with them noticeable complaints, and serious health effects usually become apparent only after many years, in adults life, as a back pain syndrome, gynecological problems in woman, respiratory and cardiovascular problems related to deformities of the chest or reduction in efficiency etc.